Econometric Analysis of the Formation of Deposit Resources of Households and Their Role in Ensuring Financial Security of the State - Dubyna, M.; Tarasenko, O.; Popova, L.; Kalchenko, O.; Safonov, Yu.; Lozychenko, O. (International Journal of Safety and Security Engineering, 2022)
Within the article, the formation of deposit resources of households and their role in ensuring financial security of the state is considered. Significant attention is paid to the formation of such resources within the financial system. To this end, a statistical analysis from 2007 to 2020 of the main trends in the formation of deposits by households in Ukraine, a study of the impact of macroeconomic factors on this process is carried out, peculiarities of the deposit market in periodic economic and political instability are substantiated. The econometric analysis of the impact of certain macroeconomic factors on the creation of these resources within the national economy was also conducted. Accordingly, the article included the national currency exchange rate, the level of the average wage and the level of the real weighted average interest rate on time deposits. The methodology for constructing a multifactor linear regression model was chosen for econometric modeling. This model was also tested for adequacy. In the article, the role of household deposit resources in ensuring financial security of the state is also described in detail, the importance of providing stable conditions for the functioning of the deposit services market in order to resist external and internal threats is substantiated.
Keywords: household, financial security, banking institution, deposit resources, savings